2020
DOI: 10.26440/ihrj/0409.12316
|View full text |Cite
|
Sign up to set email alerts
|

Infection Control in Endodontics During COVID Era: A Review

Abstract: The outbreak of the SARS-C0V-2 pandemic has continued to affect people's lives on a global scale. When the number of infected cases decreased, several countries across the world lifted their lock-down controls and started to open. But the latest re-emergence of COVID-19 cases across Europe once again prompted nations to step back to contain the virus spread. The most prevalent route of transmission is through aerosols and droplet inhalation, which is crucial for dental health workers as most dental procedures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…COVID-19's receptorbinding domain spike pattern is strikingly similar to that of SARS-CoV, and pair-wise protein sequence analysis revealed that it belonged to the SARS-related coronavirus. Both COVID-19 and SARS-CoV use the same receptor, ACE2, to enter the host cell [2].…”
Section: Transmissionmentioning
confidence: 99%
See 2 more Smart Citations
“…COVID-19's receptorbinding domain spike pattern is strikingly similar to that of SARS-CoV, and pair-wise protein sequence analysis revealed that it belonged to the SARS-related coronavirus. Both COVID-19 and SARS-CoV use the same receptor, ACE2, to enter the host cell [2].…”
Section: Transmissionmentioning
confidence: 99%
“…Respiratory droplets have a diameter of 5-10 um, while aerosols and droplet nuclei have a diameter of less than 5 um. When a person comes into close contact with an infected person who has respiratory symptoms, the virus is transmitted via these droplets [2].…”
Section: D) Droplet Transmissionmentioning
confidence: 99%
See 1 more Smart Citation